2004
DOI: 10.1523/jneurosci.5205-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Aging and the Hippocampus: How Old Rats Represent New Environments

Abstract: Spatial learning impairment in aged rats is associated with changes in hippocampal connectivity and plasticity. Several studies have explored the age-related deficit in spatial information processing by recording the location-specific activity of hippocampal neurons (place cells). However, these studies have generated disparate characterizations of place cells in aged rats as unstable ( . To reconcile these findings, we recorded place cells from aged and young rats as they repeatedly explored both a highly fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
78
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 45 publications
14
78
3
Order By: Relevance
“…With similar inconsistency, spatial representations in aged rats rotate with rotated landmarks on some occasions but not others [81]. Furthermore, rigidity can be evident in the encoding properties of CA1 cells [78][79][80][81], but this is not as invariable in CA1 as it seems to be in CA3 [82]. As we now describe further, in our model these inconsistencies in CA1 might represent shifts between dependence on CA3 inputs and direct EC inputs to the CA1 subregion.…”
Section: Ca1mentioning
confidence: 66%
See 3 more Smart Citations
“…With similar inconsistency, spatial representations in aged rats rotate with rotated landmarks on some occasions but not others [81]. Furthermore, rigidity can be evident in the encoding properties of CA1 cells [78][79][80][81], but this is not as invariable in CA1 as it seems to be in CA3 [82]. As we now describe further, in our model these inconsistencies in CA1 might represent shifts between dependence on CA3 inputs and direct EC inputs to the CA1 subregion.…”
Section: Ca1mentioning
confidence: 66%
“…Of particular importance here, numerous studies have shown that CA3 and CA1 place cells of aged rats fail to encode new spatial or task information rapidly [78][79][80][81][82]. After young rats have explored one environment until it becomes highly familiar, introduction into a novel environment typically results in the creation of a new spatial representation, reflected in spatial firing patterns of hippocampal neurons that are drastically different from those associated with the familiar environment [83,84].…”
Section: Information Processing By Hippocampal Place Cells Of Aged Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Declarative memory (memory for people, facts, and events, as well as for spatial locations) is dependent upon the medial temporal lobe system, including the hippocampal formation [11,15,39,44]. Dysfunction of this system and concomitant loss of associated learning and memory functions are well-documented at advanced ages.…”
Section: Introductionmentioning
confidence: 99%